Materials and articles in contact with foodstuffs. Plastics. Test methods for "substitute tests" for overall migration from plastics intended to come into contact with fatty foodstuffs using test media iso-octane and 95% ethanol Part 14, (15th June 1999) - British Standards Institution
No abstract available